Extended Set of GoldenBraid Compatible Vectors for Fast Assembly of Multigenic Constructs and Their Use to Create Geminiviral Expression Vectors - Dusek, Jakub; Plchova, Helena; Cerovska, Noemi; Poborilova, Zuzana; Navratil, Oldrich; Kratochvilova, Katerina; Gunter, Cornelius; Jacobs, Raygaana; Hitzeroth, Inga I.; Rybicki, Edward P.; Moravec, Tomas (Frontiers in Plant Science, 2020)
Methods for simple and fast assembly of exchangeable standard DNA parts using Type II S restriction enzymes are becoming more and more popular in plant synthetic and molecular biology. These methods enable routine construction of large and complex multigene DNA structures. Two frameworks emphasize either high cloning capacity (Modular Cloning, MoClo) or simplicity (GoldenBraid, GB). Here we present a set of novel α-level plasmids compatible with GB convention that extend GB ability to rapidly assemble more complex genetic constructs while maintaining compatibility with all existing GB parts and most MoClo parts and GB modules . With the use of our new plasmids, standard GB parts can be assembled into complex assemblies containing 1, 5, 10 and up to theoretically 50 units in each successive level of infinite loop assembly. Assembled DNA constructs can be also combined with conventional binary GB-assemblies (1, 2, 4, 8… units). We demonstrate the usefulness of our framework on single tube assembly of replicating constructs based on Bean yellow dwarf virus (BeYDV) geminivirus.